2000
DOI: 10.1164/ajrccm.161.5.9905088
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Surfactant Kinetics in Infant Respiratory Distress Syndrome: A Novel Method with Stable Isotopes

Abstract: Little is known about surfactant metabolism in newborn infants, since radioactive isotopes cannot be used in humans. We describe here a new method for studying exogenous surfactant pharmacokinetics in vivo. We measured surfactant half-life, pool size, and turnover time in eight preterm infants (gestational age: 30 +/- 2 wk; birth weight: 1,416 +/- 202 g) who were mechanically ventilated because of infant respiratory distress syndrome. We administered two doses of 100 mg/kg each of a natural porcine surfactant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 27 publications
2
84
0
Order By: Relevance
“…Thus, our data are again consistent with these studies, which suggests true differences in surfactant production between those term infants with mild and severe disease. The concomitant use of stable isotopically labeled exogenous surfactant preparations will permit the more reliable estimates of surfactant pool size necessary for fully interpreting the indices of endogenous surfactant metabolism (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our data are again consistent with these studies, which suggests true differences in surfactant production between those term infants with mild and severe disease. The concomitant use of stable isotopically labeled exogenous surfactant preparations will permit the more reliable estimates of surfactant pool size necessary for fully interpreting the indices of endogenous surfactant metabolism (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…If additional parental consent was obtained, we also measured DSPC turnover with a tracer dose of (U-13 C-PA)dipalmitoyl-phosphatidylcholine mixed with 2-5 mg/kg of Curosurf, used as a spreading agent. Administration of the tracer dose and TA collection and processing were performed as previously reported (15,31). Processed samples were stored at āˆ’80 Ā°C until analysis.…”
Section: Methodsmentioning
confidence: 99%
“…13 C-palmitate enrichment was measured by gas-chromatography-mass-spectrometry (GC-MS, 6890N-5973 inert, Agilent Technologies, Milan, Italy). Results were expressed as mole percent excess referring to a calibration curve (31,38).…”
Section: Methodsmentioning
confidence: 99%
“…Hallman et al 35 and Griese et al 36 showed an apparent phospholipid pool size of E16 mg kg -1 in human preterm neonates with RDS, by using PG as label to measure surfactant pool size. Pool size measurements in preterm infants with RDS using endotracheally administered stable isotope ( 13 C-DPPC) in combination with a treatment dose of surfactant (100 mg kg -1 ) showed an endogenous surfactant PC pool size (before treatment) ranging from 1 to 15 mg kg -1 , 37 whereas term infants without RDS have three or more times that value. 38 As synthetic rates of surfactant in preterm infants are low, it is clear that pulmonary surfactant can only be rapidly increased by surfactant replacement therapy.…”
Section: Surfactant Pool Sizementioning
confidence: 99%